The new industrial geography : regions, regulations and institutions - Barnes, Trevor J. (Routledge studies in the modern world economy, 1999)
The New Industrial Geography focuses on the most important industrial-geographical changes that have taken place in Europe and North America over the last twenty years. It brings together some of the leading scholars in the field.